Pro HTML5 Performance - Bryant, Jay.; Jones, Mike.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2012)
Pro HTML5 Performance provides a practical guide to building extremely fast, light-weight and scalable websites using fully standards compliant techniques and best practices. It strikes a balance between imparting best-practice information for when you$1 (Bre building ground up and instantly applicable techniques to help you solve issues with your existing projects. In addition to a wealth of tips, tricks and secrets you$1 (Bll find advice and code samples that elegantly layout the problems your facing and the best ways of solving them. By reading Pro HTML5 Performance you$1 (Bll squeeze every last ounch of performance from your code, giving your applications unrivalled speed and cost-efficiency.s
Keywords: Computer science; Computer Science; Computer Science, general